2017
DOI: 10.1002/hbm.23885
|View full text |Cite
|
Sign up to set email alerts
|

Association between structural brain network efficiency and intelligence increases during adolescence

Abstract: Adolescence represents an important period during which considerable changes in the brain take place, including increases in integrity of white matter bundles, and increasing efficiency of the structural brain network. A more efficient structural brain network has been associated with higher intelligence. Whether development of structural network efficiency is related to intelligence, and if so to which extent genetic and environmental influences are implicated in their association, is not known. In a longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 112 publications
(178 reference statements)
3
44
0
Order By: Relevance
“…Interestingly, preliminary evidence suggests that the associations between brain structure and cognitive performance may not be static during development. For instance, Koenis et al, 2018 observed increased correlation between cognitive performance and FA-derived metric changes over adolescence.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, preliminary evidence suggests that the associations between brain structure and cognitive performance may not be static during development. For instance, Koenis et al, 2018 observed increased correlation between cognitive performance and FA-derived metric changes over adolescence.…”
Section: Introductionmentioning
confidence: 98%
“…Both cross-sectional and longitudinal research in children and adolescents using fractional anisotropy (FA), a commonly used estimate of white matter integrity, have consistently revealed strong correlations between FA and cognitive ability using tests of working memory, verbal and nonverbal performance (Koenis et al, 2015;Krogsrud et al, 2018;Peters et al, 2014;Tamnes et al, 2010;Urger et al, 2015). There is also some evidence that the correlation between cognitive performance and FA-derived metrics increases over adolescence (Koenis et al, 2018). Moreover, recent research has also found associations between the corpus callosum (Navas-Sánchez et al, 2014;Westerhausen et al, 2018) association fibers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The human brain is composed of structural networks that support brain function via white matter fiber connections (Kanai & Rees, 2011), making white matter microstructure essential to complex cognition (Kennedy & Raz, 2009;Madden et al, 2008), development (Barnea-Goraly et al, 2005;Giedd et al, 1999;Koenis et al, 2018;Nagy, Westerberg, & Klingberg, 2004), plasticity (Hofstetter, Tavor, Moryosef, & Assaf, 2013;Zatorre, Fields, & Johansen-Berg, 2012), and successful aging (Gunning-Dixon, Brickman, Cheng, & Alexopoulos, 2009;Gunning-Dixon & Raz, 2000). White matter microstructure is influenced by several factors, especially those associated with increased innate inflammatory activity (Porter, Leckie, & Verstynen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Using a twin analysis, the authors showed that the phenotypic covariance between IQ and cortical thickness and cortical thickness change was effectively entirely genetic. Koenis et al (2018) showed (in the same sample as Koenis et al, 2015 above) age-dependent correlations between brain measures and IQ: Weak or absent correlations early in childhood (r=0 at age 10) became pronounced by middle to late adolescence (age 18, r=.23). Notably, the previous steep changes in efficiency between age 10 and 13 had levelled off by age 18, suggesting a slowing down of cortical development.…”
Section: The Role Of Geneticsmentioning
confidence: 57%